SENI REJUNG SEBAGAI SASTRA TUTUR ETNIK SEMENDE BERMUATAN NILAI BUDAYA LOKAL - Hidayatullah, Fadhilah (Besaung : Jurnal Seni Desain dan Budaya)
This article discusses the results of research on Rejung art in Tanjung Bulan village, Pulau Beringin district (OKU Selatan). The background, the need to be studied and transformed towards regeneration. Because it is rich in local cultural values. The approach used in this research is qualitative with descriptive methods. The results of this study are that there are poems that contain the value of life containing messages; advice, moral, social, religious, and aesthetic. The purpose of this research was to determine the content of the art of rejung, both express and implied. The values contained are the values of local wisdom as a guide in character education. It is recommended that further research be carried out, so that it can be used as material for the world of education, especially at the elementary school level, as material for children’s character education, because it contains the values of life with a local culture of Semende ethnicity. The art of rejung has local wisdom values contained in it. Its cultural values are more on the values of life. The value of life contained in the art of rejung which includes; values of trust and advice, moral values, religious values, and aesthetic values. The value of the mandate and advice that develops in rejung art poetry is conveyed through rejung art poetry with various titles and types of rhymes created by the artists. The mandate values contained in the lyrics are presented in the form of a vocal presentation with a variety of different kenjun. Then on the aesthetic value. The aesthetic value of the art of rejung is seen in the kenjun in each presentation. Kenjun is the rise and fall of the rejung art song melody. Kenjun can be interpreted as the value of beauty, because Semende's custom is a custom that is beautiful and peaceful, and full of affection. This is still related to the customary law rules adopted, because Semende's customary law is oriented towards Islam. His art also contains the values of life in accordance with Islamic law and law.